Determinants of international tourism: Empirical evidence from three Mediterranean countries - Emi Malaj; Visar Malaj (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: This paper investigates the main factors of international tourist arrivals to three Mediterranean destinations, namely Greece, Albania and Montenegro. Methods: A gravity model for panel data was used to analyze the number of tourists from twenty of the most important origin countries during the period 2012-2021. Results: Findings show that international tourism is adversely affected by bilateral distance and large-scale crisis such as COVID-19 pandemic. On the other hand, the flow of international visitors is positively related to populations and incomes per capita in origin and destination countries, geographical contiguity and climate similarity. Other pull factors for tourism flows include total investments in infrastructure, and political stability and absence of violence or terrorism. Implications: The results of this research provide some important implications and recommendations for tourism industry policymakers and managers.
Keywords: L83; B23; O47; 330; Mediterranean; tourism; gravity model; pull factors